Screening for Gastric Cancer: Is endoscopy the best option? - Feliz, Rosario Albis (Revista Colombiana de Gastroenterología, 2010)
The author focuses on screening for gastric cancer. She cites a study by F. Emura and colleagues published within the issue on campaigns in Bogotá, Colombia which used endoscopy with chromoscopy and narrow band imaging (NBI) to screen for premalignant lesions and cancer. The author discusses population screening and sampling and the results of a literature review she conducted, which did not show that endoscopy is a good screening method. Further analysis of the study is presented.